Factors Associated with Toddler Nutritional Status and Stunting: A Cross-Sectional Study of Maternal Knowledge, Parenting Styles, and Family Support - Desmon Wirawati; Fischa Awalin; Sumarmi Sumarmi (Journal of Health and Nutrition Research, 2026)
The nutritional status of toddlers serves as a primary indicator of public health and optimal child development. This study analyzed the relationships between maternal knowledge, parenting styles, and family support regarding toddler nutritional status in a suburban Indonesian health center. A descriptive correlational research design with a cross-sectional approach was employed, involving 242 families with toddlers aged 1–5 years selected through simple random sampling. Data were collected using a structured questionnaire and analyzed via Chi-square tests and Prevalence Odds Ratios (POR) with a 95% Confidence Interval (CI). Results revealed that 88% of toddlers had good nutritional status, despite 80.2% of mothers presenting poor knowledge levels. Bivariate analysis indicated no significant association between maternal knowledge and nutritional status (p = 0.604). However, significant relationships were identified for parenting styles (p = 0.027; POR = 2.89, 95% CI = 1.18 - 7.05) and family support (p = 0.000; POR = 8.54, 95% CI = 2.87 - 25.40). Toddlers raised with poor parenting practices or inadequate family support were significantly more likely to experience poor nutritional outcomes. This study concludes that public health interventions should prioritize strengthening family support systems and positive parenting practices over theoretical education alone. Enhancing these social determinants is crucial for optimizing early childhood growth and structural care.